Hobby and business on trading birds: Case study in bird market of Sukahaji, Bandung, West Java and Splendid, Malang, East Java (Indonesia) - BUDIAWATI S ISKANDAR; JOHAN ISKANDAR; RUHYAT PARTASASMITA (Society for Indonesian Biodiversity, 2019)
Abstract. Iskandar BS, Iskandar J, Partasasmita R. 2019. Hobby and business on trading birds: Case study in bird market of Sukahaji, Bandung, West Java and Splendid, Malang, East Java (Indonesia). Biodiversitas 20: 1316-1332. Bird species have various ecological and socio-economic-cultural functions for the human being. Ecologically, birds have beneficial functions in the ecosystem, such as helping plant pollinators, spreading plant seeds, participating in controlling agricultural pests, and monitoring environmental changes. Meanwhile, bird functions for the social-economic and culture of the community among them are known as sources of protein food, mystical functions, sources of material stories, sources of inspiration to make songs, craft materials, the source of gene pool, and become pets and trade animals. With the rise of the urban population hobby of raising birds and also the development of various bird contest activities in the urban, causing of the bird trade is very widespread in urban areas, such as in bird markets. In some cities in Indonesia, various bird markets have been popularly known for a long time. This study aimed to elucidate species diversity, folk classification, bird populations, bird prices, constraints to bird trade, and the positive and negative effects of bird trade in the urban bird market. The research method used a mixture of qualitative and quantitative methods with the ethnoecological approach. The results of this study showed that from a survey of 60 bird traders in the bird market of Sukahaji, Bandung, and Splendid, Malang, a total of 160 bird species, representing 38 families were documented. Among them, 10 species representing 7 families recorded as protected bird by law in Indonesia, based on recent government regulation of the Minister of Environment and Forestry of Republic of Indonesian No.106/MENLHK/SETJEN/KUM.1/12/2018. A total of 2,950 individuals were recorded in Sukahaji; while in Splendid were recorded 3,558 individuals. Prices of birds that are traded varied greatly depending on the species and characteristics of birds. It has been revealed that bird trade in the bird market has been various economic benefits for many people. However, due to the bird trade in bird markets in the city which has not been properly managed, the sustainability system of the bird trade in the city is very alarming caused of many factors, including decreasing of bird population over time in rural ecosystem as main supply of urban bird trading in the bird markets. Therefore, bird trading in the bird markets must be properly managed based on the sustainable development program concept, namely pro-economic, pro-social, and pro-environment.